Issues of Action Research and Adult Basic Education - Rosemarie Mincey (Adult Education Research Conference, 2000)
A three-state action research (AR) project with adult basic education (ABE) instructors led to the development of new approaches for documenting outcomes and new insights about the process of conducting AR.